Evaluation of torsion and twist mechanics of the left ventricle in patients with systemic lupus erythematosus - Bulut, Mustafa; Acar, Rezzan Deniz; Acar, Sencan; Fidan, Serdar; Yesin, Mahmut; İzci, Servet; Efe, Suleyman Cagan; Cakır, Hakan (Anatolian journal of cardiology, 2016)
Myocardial involvement in systemic lupus erythematosus (SLE) has great importance. The aim of this study is to evaluate the rotation and twisting mechanics of the left ventricle (LV) in patients with SLE. Forty-three patients fulfilled at least four of the American College of Rheumatology criteria for SLE and 30 individuals as controls were included in the study. SLE disease activity was assessed using the SELENA-SLEDAI score. Echocardiography was performed for all subjects. The patients fulfilled at least four of the American College of Rheumatology criteria for SLE were enrolled in the study. SLE disease activity was assessed using the SELENA-SLEDAI score. Echocardiography was performed for all individuals.Comparisons between groups were made using independent samples t-test with the standard statistical software (SPSS, version 15.0; SPSS Inc., Chicago, IL, USA). Each image was digitally stored for offline analysis. Measurement of global strain assessed by 17-segment model and rotational parameters were performed. LV ejection fraction was calculated by the biplane Simpson's method. Comparisons between groups were made using the independent samples t-test with the standard statistical software. A p value of 0.05 was considered statistically significant. The values of mean global longitudinal strain, basal global circumferential strain (GCS), mean basal radial strain, and apical GCS were significantly lower in SLE patients. The difference between basal rotation, apical rotation, twist of the LV, and torsion of the LV in the SLE patients and controls were not significant (8.8±5.5 vs. 10.6±5.8, p=0.183;-4.7±3.0 vs. -4.8±3.2, p=0.947; 11.7±6.4 vs. 13.2±6.4, p=0.366; and 1.8±0.8 vs. 1.9±2.3, p=0.725, respectively). Although there was not any significant relationship between SELENA-SLEDAI score and myocardial strain analyses of the LV, the basal rotation and the torsion of the LV were lower in patients with SLE having a SLEDAI score of ≥17 (p=0.024 for basal rotation and p=0.032 for torsion). The number of segmental and global strain analyses were decreased in SLE patients with globally normal LVEF. The twist and torsion mechanics of the LV were preserved according to the control group, and the left ventricular torsion and basal rotation were found to be significantly decreased in those with an activity score of ≥17.